Integrating the perspectives on language and space - Auer, Peter; Hilpert, Martin; Stukenbrock, Anja; Szmrecsanyi, Benedikt (Space in language and linguistics, 2013)
Das Kapitel Integrating the perspectives on language and space erschien in Space in Language and Linguistics auf Seite 1.